Preserved in clay: Ornamentation of Late Neolithic ceramic funerary vessels - Kaczmarek, Monika (Archaeological Textiles Review, 2023)
Knowledge about textile production in the Neolithic period is relatively poor throughout Europe. Due to the rarity of organic remains, textile imprints preserved on pottery or other fired clay artefacts are valuable sources. This paper presents the results of technical analyses and experimental research into textile impressions identified on funerary ceramics. The materials are 19 pots from archaeological sites from the Polish lowlands. Fragments are dated to the Late Neolithic period. The set of vessels analysed feature impressions of decorative textiles. These included impressions possibly made with textile constructions, but also the so-called “free-hand” cord impressions. Ornaments made using the latter method are in the majority.